Corporate Governance Reform, Board Structure, and Its Determinants in the Banking Industry—Evidence from Taiwan. Issue 9 (1st September 2016) - Lin, Kun-Li; Chang, Yuan
ABSTRACT: This study employs the data of twenty-seven banks listed on the Taiwan Stock Exchange from 2000–11 to examine the determinants of board structure, e.g., board size and the independent directors ratio. The evidence shows that bank size, the degree of revenue diversification, and the CEO's shareholding are positively associated with the independent directors ratio. A higher outside block shareholding is correlated with a larger board size and a higher independent directors ratio. As the creditors' stake decreases, a larger board and greater board independence are required to maintain internal corporate governance. Finally, banks with M&A activity tend to downsize their board sizes and reduce board independence in the subsequent period.